People's Perception on use and Management of Urban Green Spaces of Gurugram, India - Yadav, Subhash; Sarika; Yadav, Seema; Rajendra, Kushagra (Indian Forester, 2025)
This study examines three urban green spaces in Gurugram: Tau Devilal Park, Maharana Pratap Swaran Jayanti Park and Tau Devilal Biodiversity Botanical Garden. The study explored the motive and purpose of the visit, user's understanding about ecosystem services given by these spaces, willingness to pay monetary value for the ecosystem services, park upkeep, and management issues which they want the authorities to take cognizance. The results show a higher number of male visitors and young working visitors. The factors that influence park preference are large walking spaces; accessibility and biodiversity. People prefer visiting in groups for health benefits and enjoy open green spaces. Grass was the most preferred vegetation. 66% of respondents acknowledged the provisioning and regulating services provided by urban green spaces. Only 50% were willing to pay for the ecosystem benefits while 37.67% strongly disagreed with the idea. Those who supported the idea supported levying a modest fee for better maintenance and up-keep of the park. Issues faced by visitors involve poorlighting, dog-menace, safety concerns, poorly maintained or lack of basic amenities and presence of anti-social elements. Findings of the study will help authorities to align their efforts towards improving user's experience.